1984
DOI: 10.1073/pnas.81.7.2097
|View full text |Cite
|
Sign up to set email alerts
|

Proviruses are adjacent to c-myc in some murine leukemia virus-induced lymphomas.

Abstract: Sixty-one murine leukemia virus-induced lymphomas were examined for evidence of proviral insertions adjacent to known oncogenes. Five of these lymphomas were found to have alterations adjacent to c-myc. Two of the lymphomas with altered c-myc sequences were examined in detail. Evidence was obtained showing that the alterations in the cmyc sequences in these two lymphomas were the result of proviral integrations. This result suggests that lymphomagenesis by murine leukemia viruses can result from insertional mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
79
0
6

Year Published

1985
1985
1989
1989

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(86 citation statements)
references
References 27 publications
1
79
0
6
Order By: Relevance
“…The breakpoint localizainduced rat thymomas (52). In addition, c-myc regulatory tion studies showed that c-myc rearrangement in 10 of 14 elements have been proposed to reside in this region (3, 6, RICs occurred within a 1.5-kb XbaI-EcoRI fragment, which 41,46,58).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The breakpoint localizainduced rat thymomas (52). In addition, c-myc regulatory tion studies showed that c-myc rearrangement in 10 of 14 elements have been proposed to reside in this region (3, 6, RICs occurred within a 1.5-kb XbaI-EcoRI fragment, which 41,46,58).…”
Section: Methodsmentioning
confidence: 99%
“…Libraries were constructed and screened as described (28 The c-myc breakpoints cluster in a 1.5-kb region upstream of exon 1. The rat c-myc gene is located on a 17-kb EcoRI fragment which contains all three exons and 5'-and 3'-,,, _ 4 flanking sequences (34,52,53). Our previous studies have V shown that the c-myc is rearranged in four of five RICs (53).…”
Section: Methodsmentioning
confidence: 99%
“…Regulated expression of the c-myc proto-oncogene is implicated in the regulation of vertebrate cell proliferation (3,16,17,31); and aberrant expression contributes to the pathogenesis of a variety of malignancies, including lymphoid tumors of chickens (29,42), mice (1,12,14,49,54,56), and humans (1,15,56) and human small cell lung cancers (38). The normal c-myc gene of chickens (50), mice (53), and humans (5,24,59) contains three exons, the second and third of which encode the protein product.…”
mentioning
confidence: 99%
“…However, in contrast to Mlvi-1, Mlvi-2 could not be detected in hybrid HM25, suggesting that Mlvi-2 maps to the centromeric end of chromosome 15. Thus, the separation of Mlvi-J and Mlvi-2 in a hybrid apparently carrying a chromosome 15 The genetic mapping of Mlvi-J to chromosome 15 raised the possibility that this region of integration could contain the cellular oncogenes c-myc or c-sis. Both of these oncogenes have been mapped to chromosome 15 (5,13,19), and several recent studies have suggested that aberrations involving c-myc are involved in some rat and mouse viral leukemias (4,28). Our studies of rat thymomas also suggest that rearrangements c-myc may coexist in the same tumors with rearrangements in Mlvi-J (P. N. Tsichlis, P. G. Strauss, and M. Lohse, manuscript in preparation).…”
Section: S Ppepementioning
confidence: 49%
“…These and other studies on virus-associated leukemogenesis indicate that virus integration into specific chromosomal regions is an important factor in oncogenesis and that sequences on mouse chromosome 15 are probably involved in this process (4,17,19,28). The clustering of at least three genes on chromosome 15 which are associated with thymic lymphomas (Mlvi-l, Mlvi-2, and Myc) and a locus associated with mammary carcinomas (Int-1) (17,19) is particularly intriguing since aberrations of this chromosome are commonly found in murine thymic lymphomas and include trisomy 15 in most AKR thymomas (7,38) and an X;15 translocation in DMBA-induced SJL thymomas (27).…”
Section: S Ppepementioning
confidence: 99%